Bakhtin on the Nature of Dialogue: Some Implications for Dialogue between Christian Churches - Duncan Reid (Temenos, 2013)
The paper offers a contribution to the discussion of the role of intercultural issues in dialogue between Christian churches representing differing doctrinal positions. It argues that ecumenical dialogues have in the past focused on doctrinal issues at the expense of cultural differences, which may be just as significant in the relationships, including understandings and misunderstandings, between churches. It proposes that expertise on intercultural communication be also part of ecumenical dialogue. This argument shall be developed in several stages: first, a discussion of belief statements as cultural artefacts; second, a discussion of a recent study of the dynamics of intercultural communication, a study that draws on Bakhtin’s concept of dialogue; and finally the proposal for the application to ecumenical dialogue of the study’s methodological approach to intercultural communication.